Pharmacotherapy in Cardiovascular Disease with Chronic Kidney Disease Medications: A Comprehensive Literature: Cardiovascular Disease with Chronic Kidney Disease - Azhar, Maryam; Zafar, Muneeb; Irtaza, Ali; Asad, Madiha; Kim, Sajal; Walait, Manam; Mir, Huda Rehman; Walyat, Salman (Pakistan Journal of Health Sciences, 2023)
A progressive decrease of renal function is a symptom of chronic kidney disease, commonly known as chronic kidney failure. The body may accumulate hazardous amounts of fluid, electrolytes, and wastes if the patient has advanced chronic kidney disease. There are several causative factors which lead to CKD which include high or low blood pressure, more accumulation of cholesterol, diabetes and many more. According to WHO global health statistics in 2012, 864,226 mortalities (or 15% of all deaths worldwide) were attributed to this illness. CKD was categorized 14th on the index of principal causes of death, having 122 mortalities per 100,000 persons. Most of the causes of deaths were due to sudden cardiac arrests in CKD patients. In this review, we made a list of 10 FDA approved medications which has proven to decrease CKD and fatalities caused by cardiac arrests. SGLT-2 inhibitors have shown promising results in manipulating kidney functions to improve the efficiency of heart.